Diagnostic and Judicial Process Problems in Young Incest Cases Three Case Reports - Korkmaz, Saniye; Erermiş, Serpil; Tamar, Müge; Aydın, Cahide; Kayahan, Ayşe (The Bulletin of Legal Medicine, 2001)
Incest refers to the sexual abuse of a child by another family member. It is rarely reported in spite of its prevalence. Incest forces dynamic and social changes for family as well as for the child. Referrals to the child psychiatry clinics are judicial in common. The reporting procedure may be influenced not only by the mental and emotional developmental characteristics of the child but also by the family. The aim of this study is to discuss the difficulties of medicolegal reporting process of three cases who had been admitted with an alleged incest history and to suggest standard criteria for these reports. Case a is a 5,5 year-old girl with an history of alleged father-daughter incest, case B is a 5,5 year-old boy with a similar history and case C is a 4 year-old girl with a history of alleged stepfather incest. We report the social, demographic data as well as, family characterictics, present psychiatric state, psychometric examinations and, follow- up results of these three cases in order to discuss the diagnosis and judicial process. We suggest that similar studies should be carried out by multidisciplinary teams. Key words: Child, incest, judicial process